Group‐Difference Effect Sizes: Gauging the Practical Importance of Findings from Group‐Experimental Research. Issue 2 (2nd April 2018) - Cook, Bryan G.; Cook, Lysandra; Therrien, William J.
Abstract: Effect sizes are powerful tools for evaluating the practical importance of study findings that should be considered in the context of study characteristics such as participants, dependent variables, and comparison condition. In this article, we discuss how group‐difference effect sizes are used to gauge the practical importance of group experimental studies. We first define different types of group‐difference effect sizes and discuss how they can provide valuable information for research consumers. Second, we present guidelines for interpreting group‐difference effect sizes. Third, we discuss important contextual variables that should be taken into account when interpreting group‐difference effect sizes reported in the literature. Last, we provide two examples of how group‐difference effect sizes have been used in the learning disabilities research base.